Adaptive Cation Pillar Effects Achieving High Capacity in Li‐Rich Layered Oxide, Li2MnO3‐LiMeO2 (Me = Ni, Co, Mn) (Small 42/2022). Issue 42 (20th October 2022) - Hiroi, Satoshi; Oishi, Masatsugu; Ohara, Koji; Shimoda, Keiji; Kabutan, Daiki; Uchimoto, Yoshiharu
Abstract : Lithium‐Ion Batteries In article number 2203412, Satoshi Hiroi, Masatsugu Oishi, Koji Ohara, and co‐workers, discuss the pillar effect that supports the lithium layer structure upon charging in a lithium‐rich layered oxide, Lix Ni0.15 Co0.19 Mn0.50 O2, positive cathode material. The structural stability and high lithium ionic conduction are maintained by adaptive pillars formed by transition metals on Li‐tetrahedral sites.